Deep-Breathing Honeycomb-like Co-N(x)-C Nanopolyhedron Bifunctional Oxygen Electrocatalysts for Rechargeable Zn-Air Batteries - Li, Zhaoqiang (iScience, 2020)
Metal organic framework (MOF) derivatives have been extensively used as bifunctional oxygen electrocatalysts. However, the utilization of active sites is still not satisfactory owing to the sluggish mass transport within their narrow pore channels. Herein, interconnected macroporous channels were constructed inside MOFs-derived Co-N(x)-C electrocatalyst to unblock the mass transfer barrier. The as-synthesized electrocatalyst exhibits a honeycomb-like morphology with highly exposed Co-N(x)-C active sites on carbon frame. Owing to the interconnected ordered macropores throughout the electrocatalyst, these active sites can smoothly “exhale/inhale” reactants and products, enhancing the accessibility of active sites and the reaction kinetics. As a result, the honeycomb-like Co-N(x)-C displayed a potential difference of 0.773 V between the oxygen evolution reaction potential at 10 mA cm(−2) and the oxygen reduction reaction half-wave potential, much lower than that of bulk-Co-N(x)-C (0.842 V). The rational modification on porosity makes such honeycomb-like MOF derivative an excellent bifunctional oxygen electrocatalyst in rechargeable Zn-air batteries.